Реактивные особенности нервного аппарата надпочечных желез некоторых обезьян при облучении - Агарков, Г.Б. (Вестник зоологии, 1969)
The article deals with the new data of the response of nerve structures of Macacus rhesus suprarenal glands to long (1 year) effect of small doses (2—3 R) of X-rays during total irradiation of animals (the total dose—1000 R). Alongside with intact nerve structures the nerve elements are found, which were subjected to such reactive changes as hyperimpregnation, hypertrophy, neuroplasm influxes and vacuolization, ft testifies to the participance of suprarenal nervous apparatus of the animals under experiment in adaptation reactions during radioactive disease of organs.